Functional Response and Control Potential of Orius sauteri (Hemiptera: Anthocoridae) on Tea Thrips (Dendrothrips minowai Priesner) - Qiuping Zhang; Ruifang Zhang; Qiuqiu Zhang; Dezhong Ji; Xia Zhou; Linhong Jin (Insects, 2021)
This study aimed to clarify the functional response and control potential of O. sauteri in relation to tea thrips. The functional response, interference response, and control potential of O. sauteri on adult tea thrips, in different insect stages and environment temperatures, were studied. The results showed that the predation of O. sauteri against tea thrips was positively correlated with prey density, while the effects of searching for O. sauteri on the adult tea thrips were negatively correlated with prey density. The predation effects of O. sauteri on tea thrips were also influenced by prey density, which indicated that there was an intra-specific interference response from predators to tea thrips. The population density of tea thrips was significantly decreased, and O. sauteri showed a remarkable ability to control them when the benefit-to-harm ratio was 3:100.